Are adolescents who consume pornography different from those who engaged in online sexual activities?. (April 2020) - Efrati, Yaniv; Amichai-Hamburger, Yair
Highlights: Solo and partnered sexual activities might be extrapolated to the virtual arena. Adolescents consuming pornography vs other forms of cybersex have distinct profiles. Differences were found on psychological and cultural factors. Abstract: Research has indicated several differences between those who solely engaged in online pornography use and those who mainly engaged in partnered sexual activities. We examined whether the distinction between solo and partnered sexual activities might be extrapolated to the virtual arena, while studying the psychological differences between adolescents who engaged in each activity. Israeli adolescents ( N = 2112; 788 boys and 1, 324 girls), age 14–18 ( M = 16.52, SD = 1.63), participated in an online study. Each participant completed a randomly ordered battery of self-report questionnaires on frequency of pornography use, sexually related online activities, personality traits, narcissism, emotion regulation strategies, social intimacy and socio-demographic factors. Adolescents who consumed pornography (i.e., solo online activity) are mostly boys, introvert, neurotic, less agreeable, and with less conscientious judgement. In addition, they are more overt narcissist, use more suppression and less reappraisal to regulate emotions, and are low on social intimacy. Adolescents who engaged in online partnered sexual activities are mostly girls, extrovert, open to experience, neurotic, less agreeable, and with less conscientious judgement. In addition, they are more narcissist and high on social intimacy. We discuss the distinctiveness of the differences and their place in the virtual era.